2015
DOI: 10.1016/j.afjem.2015.03.001
|View full text |Cite
|
Sign up to set email alerts
|

Buccal, intranasal or intravenous lorazepam for the treatment of acute convulsions in children in Malawi: An open randomized trial

Abstract: Introduction: Acute convulsions in children are a common emergency worldwide. Benzodiazepines are the recommended first line treatment. Intravenous lorazepam is inexpensive, long acting and the first line drug in resource-rich settings. However, comparable efficacy by other routes of administration is unknown. We wished to compare the efficacy of lorazepam by the buccal, intranasal or intravenous route in the treatment of acute seizures in Malawian children. Methods:A prospective, open-label, randomised, non-i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 44 publications
(48 reference statements)
0
4
0
1
Order By: Relevance
“…The mean weights in our study were 24.06 kg and 24.51 kg in the IN and IV groups, respectively. In Lissauer et al 19 , the mean weights were 10 kg and 10.4 kg in the IN and IV groups, respectively. 19 The studied children aged 2 months to 14 years had shown that intranasal lorazepam was less effective than the IV lorazepam as a first-line treatment for acute seizures but may be useful in children without or with difficult IV access.…”
Section: Discussionmentioning
confidence: 86%
See 3 more Smart Citations
“…The mean weights in our study were 24.06 kg and 24.51 kg in the IN and IV groups, respectively. In Lissauer et al 19 , the mean weights were 10 kg and 10.4 kg in the IN and IV groups, respectively. 19 The studied children aged 2 months to 14 years had shown that intranasal lorazepam was less effective than the IV lorazepam as a first-line treatment for acute seizures but may be useful in children without or with difficult IV access.…”
Section: Discussionmentioning
confidence: 86%
“…In Lissauer et al 19 , the mean weights were 10 kg and 10.4 kg in the IN and IV groups, respectively. 19 The studied children aged 2 months to 14 years had shown that intranasal lorazepam was less effective than the IV lorazepam as a first-line treatment for acute seizures but may be useful in children without or with difficult IV access. 19 In our study, with respect to seizure control, INLOR is not inferior to the current standard of practice IVLOR.…”
Section: Discussionmentioning
confidence: 86%
See 2 more Smart Citations
“…Zudem ist Buccolam ® seinerseits nicht für Erwachsene zugelassen und lässt sich nicht auf das Milligramm genau, sondern nur in festgelegten Dosierungsschritten applizieren [11]. Es mehren sich zudem Hinweise, dass die bukkale Resorption und konsekutiv die klinische Wirkung im Vergleich zur nasalen langsamer verläuft [12,13].…”
unclassified